Hospitalization in Pediatric Diabetes: A Nationwide Analysis of all Admission Causes for Germany in 2015 - Auzanneau, Marie; Rosenbauer, Joachim; Icks, Andrea; Karges, Beate; Neu, Andreas; Ziegler, Ralph; Marg, Wolfgang; Kapellen, Thomas; Holterhus, Paul-Martin; Holl, Reinhard W. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Introduction Regarding pediatric diabetes, hospital admission for acute complications of type 1 diabetes (T1D) has often been investigated, but little is known about other causes of hospitalization. This study aimed to explore the total burden of hospitalization in individuals with diabetes<20 years of age in Germany.Methods Using the German Diagnosis-Related Groups data for 2015, we examined the frequencies of hospitalization with diabetes (20 251 inpatient cases), stratified by diabetes type [T1D, type 2 diabetes (T2D), other specified diabetes types (T3D), and unclear diabetes], and without diabetes (1 269 631 inpatient cases). Using estimates of the population at risk with T1D, T2D, and without diabetes, we evaluated hospitalization rates (per patient-year) by Poisson regression. For T1D, T2D, and T3D, we investigated the most frequent diagnoses and the median length of stay. Most analyses were stratified by sex, age-group and east/west residence.Results Children and adolescents with diabetes had a 6 to 9 times higher hospitalization risk than peers without diabetes (hospitalization rate 0.09). The hospitalization rate was higher for T2D compared with T1D (0.84 vs. 0.53, P<0.001). In T2D, two-third of inpatient cases were not directly related to diabetes, and stay was shorter compared with T1D and T3D (3 vs. 4 and 5 days, respectively). In T1D, hospitalization was more frequent among girls than boys (0.58 vs. 0.49, P<0.001), and mostly due to “diabetes without complications” (65.7%). Hospitalization tended to be more frequent and longer in the youngest patients, and in those with east residence.Conclusion Hospitalization rate in pediatric diabetes in Germany remained high, especially for T2D patients, girls with T1D, and young children.
Keywords: Type 1 diabetes; type 2 diabetes; pancreatic diabetes; comorbidities; secondary data analysis; German DRG.